2022
DOI: 10.3390/ijms231911759
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Small Heat Shock Proteins in Protein Misfolding Associated Motoneuron Diseases

Abstract: Motoneuron diseases (MNDs) are neurodegenerative conditions associated with death of upper and/or lower motoneurons (MNs). Proteostasis alteration is a pathogenic mechanism involved in many MNDs and is due to the excessive presence of misfolded and aggregated proteins. Protein misfolding may be the product of gene mutations, or due to defects in the translation process, or to stress agents; all these conditions may alter the native conformation of proteins making them prone to aggregate. Alternatively, mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 308 publications
0
5
0
Order By: Relevance
“…Skeletal muscle represents the main tissue for glutamine synthesis, storage, and release [74]. Glutamine has antioxidant (as a precursor of glutathione) and anti-inflammatory properties, modulates the synthesis of shock proteins [74], which are implicated in the response to the proteostatic stress in ALS and other neurodegenerative disorders [75], and participates in skeletal muscle differentiation [76]. However, during catabolic situations, as might occur in the muscle of ALS patients [74,77], glutamine concentration in plasma and tissues (especially in skeletal muscle) is severely compromised [78].…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal muscle represents the main tissue for glutamine synthesis, storage, and release [74]. Glutamine has antioxidant (as a precursor of glutathione) and anti-inflammatory properties, modulates the synthesis of shock proteins [74], which are implicated in the response to the proteostatic stress in ALS and other neurodegenerative disorders [75], and participates in skeletal muscle differentiation [76]. However, during catabolic situations, as might occur in the muscle of ALS patients [74,77], glutamine concentration in plasma and tissues (especially in skeletal muscle) is severely compromised [78].…”
Section: Discussionmentioning
confidence: 99%
“…The chaperon-assisted proteasome degradation is a system that facilitates the degradation of abnormal proteins by bridging misfolded and aggregated proteins to heat shock protein 70 (HSP70). This system participates in maintaining the protein homeostasis and promotes the refolding or removal of potentially toxic proteins ( Tedesco et al, 2022 ). It has been found that heat shock proteins are encapsulated in the SOD1-positive aggregates, which reduces their ability to process the misfolded proteins in ALS ( Farrawell and Yerbury, 2021 ).…”
Section: Imbalance Of Protein Homeostasis In Neuronsmentioning
confidence: 99%
“…16 sHsps known as 'housekeeping' proteins represent a group of highly conserved molecular chaperones that bind to misfolded proteins during stress conditions to prevent irreversible protein unfolding or aggregation, thereby maintaining protein homeostasis. [17][18][19] sHsps perform their chaperone-like activity in an ATP-independent manner. 18 sHsps have been widely studied in ticks.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they are involved in protein folding, assembly, secretion, and degradation as well as the regulation of various cellular functions in organisms 16 . sHsps known as ‘housekeeping’ proteins represent a group of highly conserved molecular chaperones that bind to misfolded proteins during stress conditions to prevent irreversible protein unfolding or aggregation, thereby maintaining protein homeostasis 17–19 . sHsps perform their chaperone‐like activity in an ATP‐independent manner 18 .…”
Section: Introductionmentioning
confidence: 99%